2016
DOI: 10.1080/13607863.2016.1191060
|View full text |Cite
|
Sign up to set email alerts
|

Living alone and depression: the modifying role of the perceived neighborhood environment

Abstract: Objective Older adults who live alone are more likely to report feelings of depression than those who live with a spouse or other family members. This study examines the effects of residential status and perceived neighborhood characteristics on depression in middle-aged and older adults. Methods This study is based on a probability sample of 1049 adults aged 55–98 years (M = 69 years) residing in Allegheny County, Pittsburgh, PA, USA in 2014. Thirty percent of participants reported living alone. We tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
109
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 23 publications
15
109
3
4
Order By: Relevance
“…A recent report by the Ministry of Health and Welfare in Korea () indicated that 30.2% of older adults living alone had depressive symptoms, while 16.4% of those living with partners and 21.7% of those living with adult children experienced the same. The vulnerability of this population to depression is also well noted in other countries; studies routinely find that older adults living alone are more likely to experience depression than those living with other family members (Stahl, Beach, Musa, & Schulz, ; Xiu‐Ying, Qian, Xiao‐Dong, Xue‐Mei, & Chang‐Quan, ).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…A recent report by the Ministry of Health and Welfare in Korea () indicated that 30.2% of older adults living alone had depressive symptoms, while 16.4% of those living with partners and 21.7% of those living with adult children experienced the same. The vulnerability of this population to depression is also well noted in other countries; studies routinely find that older adults living alone are more likely to experience depression than those living with other family members (Stahl, Beach, Musa, & Schulz, ; Xiu‐Ying, Qian, Xiao‐Dong, Xue‐Mei, & Chang‐Quan, ).…”
Section: Introductionmentioning
confidence: 66%
“…Weakened or absent social relationships among older adults is considered a serious public health issue (Liu, Ozodiegwu, Yu, Hess, & Rie, ), as it is known to increase the risk of depression (Chou et al, ; Kim, ; Park, ; Lee et al, ; Stahl et. al., ). Studies examining depression among older adults both in Korea and other countries have note that reduced social participation, social networks, and social support are strongly associated with an increased risk of depression (Arslantas et al, ; Chang & Kim, ; Chou et al, ; Dean, Kolody, Wood, & Matt, ; Lee et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The elderly who live alone have fewer chances to communicate with others (Margolis & Verdery, 2017). It could make the person feel lonely and depressed (Stahl, Beach, Musa, & Schulz, 2017). This would have a negative effect on maintaining cognitive function in the elderly living alone.…”
Section: Discussionmentioning
confidence: 99%
“…de um ente querido resulta em isolamento social e solidão, que são fatores de risco significativos para a saúde mental e baixa qualidade de vida. 18 Por outro lado, no grupo proveniente da internação foi observado 23,1% de divorciados. Provavelmente, estes pacientes, devido ao seu próprio perfil, tinham mais dificuldade de manter relações interpessoais.…”
Section: Discussionunclassified